COVID-19 telephone contact tracing in Flanders as a “contested” new genre of conversation: Discrepancies between interactional practice and media image - Bafort, Anne-Sophie; De Timmerman, Romeo; Van de Geuchte, Sofie; Slembrouck, Stef; Vandenbroucke, Mieke (Frontiers in Communication, 2023)
During the Covid-19 pandemic in Belgium, most Covid-19-related information was communicated to the public through mainstream media such as newspaper outlets, television, and radio. These media had substantial influence over which information was (widely) distributed and how this information was framed, subsequently shaping citizens’ interpretations of matters concerning the pandemic. This chapter considers one of the government’s endeavors to contain the pandemic: Covid-19 telephone contact tracing. Specifically, we compare the image of such telephone contact tracing generated by the media with the de facto interactional practice. We report on analyses made as part of a one year applied conversation analytic and pragmatic study conducted at Ghent University and the University of Antwerp in collaboration with the Flemish Agency of Health and Care. In doing so, through thematic content analysis we examine the portrayal of Covid-19 telephone contact tracing in widespread Flemish newspapers and its evolution throughout the pandemic. We then compare this media analysis to our analysis of a corpus of 170 recorded, transcribed, and interactionally analyzed contact tracing calls, and, in particular, we demonstrate how the mainstream media’s image of contact tracing does not align with the various (interactional) functions of Covid-19 contact tracing calls identified in the study. We argue that this one-sided, distorted image produced by the media may have had considerable consequences for the efficacy of contact tracing, especially because the contact tracing call was a new genre of conversation. It was introduced to the public almost exclusively through mainstream media and, at the same time, its success relied for the most part on citizens’ voluntary participation, trust, and willingness to share private information.